Small additions of actived Biochar from palm oil shells to Portland cement mortar (2019)
Biochar is a solid material obtained from the thermochemical conversion of biomass in a limited oxygen environment. Portland cement-based products are the main construction materials. The manufacturing process of cement result in several harmful emissions, in particular CO2 emissions. In this work, biochar was produce from residues of palm oil shells stover at 700°C under a limited oxygen condition. Biochar small additions of 0.1, 0.33 and 0.5 % (w/w) were incorporated into Portland cement mortar samples. Mortar samples were made according to the Colombian earthquake-resistant standard. Early compression strength of samples were evaluated at 7, 14, 21 and 28 days. Mortar samples were subjected to an accelerated carbonation test using a carbonation chamber built for that purpose. Results shows that the early compression strength was altered since mortar with no biochar additions exhibit higher compression resistance that the ones exhibited by samples with small additions. Furthermore, this decreasing in the early compression strength is attributed to the presence of the surfactant used to incorporate the small amount of biochar into the cement matrix. Carbonation result shows that samples with small additions of biochar increases the measured carbonation depth. © Published under licence by IOP Publishing Ltd.